Soldiers as citizens : popular politics and the nineteenth-century British military - Mansfield, Nick (Historian) (Studies in labour history (Liverpool University Press), 2019)
This is the first exploration of the British army to combine labour, political and military history. It analyses the political lives of nineteenth century rank and file soldiers in the context of a developing working-class culture. It focuses on the significant radical and socialist movements, alongside influential working-class conservatism.